Experience of amplitude-frequency estimation of ground vibrations in the range of 0,05–0,5 Hz using the sensing element of the GNU-KV gravimeter - A. P. Belov; A. M. Lobanov; A. M. Erokhin (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The responsive element of the GNU-KV Russian gravimeter comprises a Golitsyn lowfrequency vertical seismograph, which outperforms modern industrial SM-3KV seismographs in terms of sensitivity to ground vibrations. A team of geophysicists at the Sergo Ordzhonikidze Russian State University for Geological Prospecting modified the construction of GNU-KV to adapt this device to work in the mode of a portable seismological station for recording natural seismic vibrations in the frequency range of 0.05–0.5 Hz. Given the equivalence of gravitational and inertial fields, the presented technology is capable of not only detecting low-frequency ground vibrations, but also estimating accelerations and amplitudes of ground displacement at these frequencies.Aim. To investigate the capabilities of the GNU-KV gravimeter for recording and estimating the amplitude of ground vibrations in mm and mGal.Materials and methods. The proposed method for determining the anomalous areas of increased ground vibration using a GNU-KV gravimeter was tested in two geographical sites: in the vicinity of the Educational and Laboratory Complex of Sergo Ordzhonikidze Russian State University for Geological Prospecting and in the area of the RUDN University near a subway tunnel.Results. When determining the amplitude of ground vibrations in mm and their acceleration in mGal, the conversion coefficient for the results of a digital signal obtained by GNU-KV and inertial accelerations in mGal was determined.Conclusion. The conducted studies confirm the capabilities of the GNU-KV gravimeter for the quantitative estimation of ground vibrations.